Genotype and phenotype association in Leber’s hereditary optic neuropathy - L. Matukynaitė; R. Liutkevičienė; A. Gelžinis; R. Žemaitienė (Neurologijos seminarai)
Leber’s hereditary optic neuropathy (LHON) is one of the most common hereditary mitochondrial optic neuropathies characterized by bilateral, painless, subacute or acute loss of central vision. The disease usually develops between the ages of 15 and 35. The majority of LHON patients are men (about 90%). LHON prevalence is commonly associated with the three most common point mutations in the mitochondrial deoxyribonucleic acid (mtDNA): m.11778 G>A, m.14484 T>C, m.3460 G>A. Point mutations that occur in deoxyribonucleic acid leads to mitochondrial respiratory chain I complex damage in all main known mutations. In this article, we review associations between the genotype and phenotype of LHON with the various mtDNA mutations in patients with LHON.